The bony cap and its distinction from the distal phalanx in humans, cats, and horses - Shannon Smith; Laurel R. Yohe; Nikos Solounias (PeerJ, 2023)
It has been recognized as early as the Victorian era that the apex of the distal phalanx has a distinct embryological development from the main shaft of the distal phalanx. Recent studies in regenerative medicine have placed an emphasis on the role of the apex of the distal phalanx in bone regrowth. Despite knowledge about the unique aspects of the distal phalanx, all phalanges are often treated as equivalent. Our morphological study reiterates and highlights the special anatomical and embryological properties of the apex of the distal phalanx, and names the apex “the bony cap” to distinguish it. We posit that the distal phalanx shaft is endochondral, while the bony cap is intramembranous and derived from the ectodermal wall. During development, the bony cap may be a separate structure that will fuse to the endochondral distal phalanx in the adult, as it ossifies well before the distal phalanges across taxa. Our study describes and revives the identity of the bony cap, and we identify it in three mammalian species: humans, cats, and horses (Homo sapiens, Felis catus domestica, and Equus caballus). During the embryonic period, we show the bony cap has a thimble-like shape that surrounds the proximal endochondral distal phalanx. The bony cap may thus play an inductive role in the differentiation of the corresponding nail, claw, or hoof (keratin structures) of the digit. When it is not present or develops erroneously, the corresponding keratin structures are affected, and regeneration is inhibited. By terming the bony cap, we hope to inspire more attention to its distinct identity and role in regeneration.